Smallholders' use of Bt-cotton under unfavourable context: lessons from South Africa - (:unkn) unknown (My University, 2008)
The bulk of the South African cotton crop is produced by large scale commercial farmers. Therefore it might be misleading to present South Africa's impressive Genetically Modified Cotton (GMC) adoption figures as evidence of successful GMC use by smallholder farmers. The total South African cotton area and number of farmers decreased drastically since the introduction of GMC and this causes observers to question the so-called success story of GMC in South Africa. Nevertheless, the smallholders' commitment in using Bt-cotton has been real and still is. Several assessment studies have demonstrated how profitable the adoption of Bt-cotton could be, but they did not take into account the local context of agriculture. The study we have implemented during the 2002/03 cropping season took place in a year of erratic rainfalls and when the institutional framework of cotton production has furthermore evolved negatively. Our study hence provides additional information on the adoption of Bt-cotton when context turns to become unfavourable. In this case, the mere access to cotton production is restrained to a limited number of producers; the cotton production becomes financially more risky while the profitability of using Bt-cotton is nullified. The South African cotton sector struggles in an unstable production and market environment and smallholders, with limited resources and limited production, managerial and marketing capacity and choice, suffer most. Technology introduction on its own cannot sustainably increase production; factors like institutional arrangements play a vital role. This reminds us that rain-fed agriculture remains sensitive to climatic hazards and that new technology adoption under these conditions might increase financial risk associated with cotton production.
Keywords: African Research